Mapping and analyzing the scientific literature on drug abuse - Varmazyar, Reza; Rahimi, Alireza; Shirshahi , Saeid (AWARI, 2023)
This scientometric study provides a comprehensive analysis of drug abuse research within the top 10 countries indexed in the Web of Science from 2010 to August 2023. It highlights the significant contributions of authors like Kendler KS and institutions such as the University of California System, emphasizing the pivotal role they play in advancing our understanding of drug abuse. The United States, China, and Iran emerge as leading contributors, with funding predominantly provided by institutions like the United States Department of Health and Human Services, NIH USA, and NIDA. The study identifies four distinct research clusters focusing on alcohol, cocaine, opioids, and cannabis, offering nuanced insights into specific areas of emphasis within drug abuse research. These findings underscore the need for collaborative, multi-faceted approaches involving researchers, institutions, and countries to effectively address the complex challenges posed by drug abuse. Building upon these insights, future research and policy initiatives can work towards more effective strategies for prevention, intervention, and support, ultimately contributing to improvements in public health and well-being.